Biologically-Inspired (Botany) Mobile Agent Based Self-Healing Wireless Sensor Network - Vasaki , Ponnusamy; Azween, Abdullah (2010)
Sensor networks are gaining popularity in pervasive environment for tracking events such as habitat monitoring, weather monitoring, hazard detection etc. These sensor nodes are very much power constrained and therefore requires energy efficient protocol to well manage their energy resources. An architecture based on biologically-inspired (botany) mobile agent based sensor (BIMAS) is proposed to tackle the energy issues of sensor networks. BIMAS handles the energy issues by exploiting mobile agents that communicates with static sensor nodes and forwards sensed data to a base station. The introduction of mobile agents brings benefit in terms of shifting routing issues away from sensor nodes to mobile agents. The advantage of BIMAs can be shown in terms of efficient energy resources, fault-tolerance and efficient handling of hole problems.